A novel pectic polysaccharide-based hydrogel derived from okra (Abelmoschus esculentus L. Moench) for chronic diabetic wound healing. (19th January 2023) - Maalej, Hana; Maalej, Amina; Bayach, Asma; Zykwinska, Agata; Colliec-Jouault, Sylvia; Sinquin, Corinne; Marchand, Laetitia; Ktari, Naourez; Bardaa, Sana; Ben Salah, Riadh; Chamkha, Mohamed; Boufi, Sami; et al.
Graphical abstract: Highlights: RG-I pectic polysaccharide (OPS) was extracted and purified from okra pods. Physico-chemical features of OPS were elucidated by FTIR, GC, SEC-MALLS and NMR. OPS solution exhibited a gel-like behavior. OPS demonstrated notable antioxidant capacity and stimulated cell migration and proliferation. OPS hydrogel effectively accelerated wound healing in alloxan-induced diabetic rats. Abstract: Hydrogels based on natural polysaccharides represent a growing group of suitable biomaterials for the elaboration of effective wound healing dressings, especially for the treatment of chronic wounds. This work was intended to prepare a polysaccharide-based hydrogel for diabetic wound healing which would help maintain the well-being of diabetes and improve their quality of life. For this purpose, a pectic polysaccharide (OPS) was extracted and purified, for the first time, from Tunisian okra pods and its physicochemical and rheological features, antioxidant and in vivo and in vitro wound healing activities were investigated. OPS, an acidic polysaccharide with a molecular weight of 3.28 × 10 6 Da and a polydispersity index of 1.03, was mainly composed of galactose (24.45 %), galacturonic acid (24.6 %) and rhamnose (18.25 %). Combined with FT-IR and NMR analyses, it consisted of a pectic rhamnogalacturonan I (RG-I) structure with galactan side chains. The OPS demonstrated antioxidant potential, gelling ability, cytocompatibility properties, non-cytotoxicity and cell migration and proliferation promoting activities, which met the requirements for wound dressings. Then, the i n vivo cutaneous wound healing effect of OPS-based hydrogel was investigated using an alloxan-induced diabetic rat model, and results showed that it significantly accelerated the wound healing process by acting in the acceleration of the recovery of the dermis and inducing more blood vessels formation and tissue granulation. Overall, these results provide new insights into the development of a promising and effective okra pectin-based hydrogel for the treatment of chronic diabetic wounds.